Evaluation of Ten Cases of Juvenile Polyp - Hara, K.; Iwanaga, S.; Fukuda, H.; Mizuta, Y.; Osabe, M.; Kubo, K.; Imanishi, T.; Matsunaga, K.; Yamasaki, K.; Makiyama, K.; Funatsu, S.; Murata, I.; et al. (Nippon Daicho Komonbyo Gakkai Zasshi, 1988)
Ten cases of juvenile polyp polypectomized endoscopically were evaluated. The age of the patients ranged from 15 to 78 years, with a mean age of 47.6 years. All patients had a single polyp. Of the ten polyps, six were located in the right side of the colon, contrary to the well accepted concept most that polyps occur in the rectum and sigmoid colon. Because of the distribution of polyp in our cases, bloody stool, which is the most common symptom of juvenile polyp, was observed in only two cases. Endoscopically, most of these polyps showed a reddish, smooth and poorly lobulated surface. Recently, the malignant potential of this type of polyp has been discussed by some authors. In our present cases, no malignant change was observed, although adenomatous foci were observed in three cases. Therefore, histological examination should be done carefully in such cases.